Change Leadership in Higher Education - Jeff Buller (Academic Chairpersons Conference Proceedings, 2017)
A highly interactive session dealing with why change is so difficult in higher education and how we can be more effective in implementing needed changes. Based on the latest studies of effective change in higher education, participants will come away from this session with a practical plan for overcoming their own resistance to change and bringing others on board when change has to occur in their program or at their institution.
Keywords: change leadership strategic planning innovation buller scenario